Implikasi Pragmatisme dan Eksistensialisme dalam Pendidikan - Wijayanti, Anti; Fadjarajani, Siti (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Abstract. Pragmatism, which emphasizes the application of knowledge through practical experience, and existentialism, which prioritizes individual freedom and self-reflection, both offer rich perspectives in shaping holistic education. The aim of this article is to examine how these two philosophies can be applied in the context of education to enhance student engagement, encourage personal development, and prepare them for the challenges of modern life. This research employs a literature review method, exploring various related literatures including books, journals, and scholarly articles to understand the application of pragmatism and existentialism in education. The findings of the research indicate that the integration of these two philosophies can create a more dynamic and meaningful learning environment, which not only hones students' technical skills but also strengthens their self-awareness and personal responsibility. In conclusion, an educational approach that combines elements of pragmatism and existentialism can produce individuals who are better prepared to face the real-world challenges with confidence, a clear sense of purpose, and critical thinking skills.